Cryptic intron activation within the large exon of the mouse polymeric immunoglobulin receptor gene: cryptic splice sites correspond to protein domain boundaries. - Bruce, S R (1999)
The fourth exon of the mouse polymeric immuno-globulin receptor (pIgR) is 654 nt long and, despite being surrounded by large introns, is constitutively spliced into the mRNA. Deletion of an 84 nt sequence from this exon strongly activated both cryptic 5' and 3' splice sites surrounding a 78 nt cryptic intron. The 84 nt deletion is just upstream of the cryptic 3' splice site; the cryptic 3' splice site was likely activated because the deletion created a better 3' splice site. However, the cryptic 5' splice site was also required to activate the cryptic splice reaction; point mutations in either of the cryptic splice sites that decreased their match to the consensus splice site sequence inactivated the cryptic splice reaction. The activation and inactivation of these cryptic splice sites as a pair suggests that they are being co-recognized by the splicing machinery. Interestingly, the large fourth exon of the pIgR gene encodes two immunoglobulin-like extracellular protein domains; the cryptic 3' splice site coincides with the junction between these protein domains. The cryptic 5' splice site is located between protein subdomains where an intron is found in another gene of the immunoglobulin superfamily.